(3GdJQhjL (B:s (3GdeaGgje(B-(3GdESJQGJjLjGJ(B-(3GdYedjGJ(B((3GdfXQjI hGdJWHjb(B) /s - (3CHhYdaI, YUGe GdOjf Cejfs ((3GdGScfOQjI(B: s (3eDSSI MhQS(B, s, 2002)
(3GdGJUGdGJ GdJShjbjI hGdJQhjL,GdGJUGdGJ GdJShjbjI,GdJQhjL(B-(3GdGYdGf(B-(3GdeaGgje(B-(3GdGSJQGJjLjGJ(B-(3GdYedjGJ,eaghe hWHjYI GdGYdGf,JUeje GdGYdGf,GdQSGdI GdGYdGfjI,GSJQGJjLjGJ GdhSGFd GdGYdGfjI,JNWjW GdMedI GdGYdGfjI,ejRGfjI GdGYdGf,bjGS aYGdjI GdGYdGf,GdOYGjI(B/(3GdfTQ,JfTjW GdeHjYGJ,GdHjY GdTNUj,GdJShjb GdeHGTQs
(3HjHdjhZQGajG(B: (3U(B.298s
Keywords: (3GdGYdGfs; (3GdJQhjLs; (3GdJShjbs